Perbandingan Motion Graphic dan Leaflet terhadap Peningkatan Pengetahuan Ibu Rumah Tangga dalam Menyimpan Obat - Nanda Puspita; Fatiyah Syahida (Politeknik Kesehatan Tanjung Karang, 2020)
Inadequate storage of medicines at home is a common health problem in the community. Therefore, it is important to promote this issue through interesting media to increase knowledge related to medication storage. This study aims to compare conventional media (leaflet) with motion graphics in increasing knowledge of drug storage at home. Quasi-experimental research with a pretest-posttest design was applied to 45 housewives with similar education levels. In the initial stage, the leaflet group (23 people) and the motion graphic group (22 people) were given a pretest about medication storage, then were intervened with the media for 5 minutes, we're given a post-test afterward. The results showed there were significant differences in medication storage knowledge between groups that were exposed to motion graphics and leaflets (p-value=0,029). The median score of the knowledge in the motion graphic group was significantly higher (85,71) than the leaflet group (71,43). Motion graphics might be beneficial as an educational media to deliver message related to effective drug management for the community, especially housewives.